Alfabetização de jovens e adultos: representações sociais de professores da EJA - Silva, Jéssica Lira da (2020)
This research aims to investigate the social representations about literacy of YAE (Youth and Adult Education) teachers and their repercussions on literacy practices. It was carried out with teachers who work with the first segment of Youth and Adult Education, in two educational institutions in the city of Natal / RN. The theoretical bases used are centered on studies on literacy; Youth and Adult Education and Theory of Social Representations (Moscovici, 1961). The theoretical-methodological path of the study is based on the Theory of Social Representations because it offers understanding of the processes of elaborating representations about adult literacy and the reverberation of these representations in pedagogical behaviors. Therefore, the research is characterized as a qualitative exploratory study. The construction of the data took place through the application of the research instruments: semi-structured interviews; non-participatory observations and a questionnaire applied to teachers. The analysis and discussion of the data are based on the assumed theoretical approach, based on the assumptions of the content analysis of Bardin (2011) and on the interpretive axis of Arruda (2005). The results, outcomes of the analysis of the triangulation of the data, issued by the participants show that there is no shared common social representation. There are variations and contrasts between and within groups. In the first group, there is greater familiarity with the object of representation and a greater approximation with the practices of literacy for young people and adults. In the second group there is a hybrid representation, based both on aspects of the reified universe and common sense and, consequently, greater distance from adult literacy practices. The representations apprehended are anchored in different elements, the main one being the initial training and the length of experience in Youth and Adult Education. Objectification also translates in different ways in the behavior of each study participant. The relevance of this research is centered on the social relevance of the topic, since it will bring contributions to the training institutions to rethink their curricula with regard to the training of teachers who will work with YAE, given that the research pointed out as the main constituent element of representation literacy training initial training in undergraduate courses.